Personal competency of women project managers / Mastura Jaafar and Liyana Othman - Jaafar, Mastura; Othman, Liyana (2012)
Women have been underrepresented in construction industry worldwide. While there are many studies done in different countries on women in construction industry, but it is interesting to note that the similar study has attracted very minimal attention in Malaysia. Studies on women involvement in the industry is rather limited. Thus, the aim of the research is to assess the personal competency level of women project managers in Malaysian Construction Industry. This study used stratified random sampling design on the listed Grade 7 Contractor companies in Peninsular Malaysia. A Survey survey approach was used to collect data from on 15 women project managers in Peninsular Malaysia. The results reveals that experience is the first criterion been used in selecting women project manager while the three main personal competencies owned by them are honesty and integrity, alertness and quickness and effective decision making.